Experimental evaluation of flexural behaviour of rubberized concrete beam - Abu Bakar, Nabilah; Noaman, Noaman Mohammed Ridha; Mohd. Nasir, Noor Azline; Safiee, Nor Azizi (Springer, 2019)
Alternative sources for cement and fine aggregate in concrete production have been studied by many researchers. In this study, the effects of rubber and pozzolana as fine aggregate and cement replacement, respectively, have been studied in terms of its compressive strength, modulus of elasticity and behaviour under flexural load. Three concrete mixes were studied, namely (1) control mix, (2) concrete with crumb rubber (rubberized concrete) and (3) rubberized concrete with pozzolana. The results show a decrease in compressive strength and modulus of elasticity by 22% and 7%, respectively, with the incorporation of rubber. The addition of pozzolana further reduces the strength, due to low reactivity of pozzolana at an early stage, causing the pozzolan to contribute mostly as a filler material. The reinforced concrete beams with the different mixes were investigated under four-point bending. The reduction in the flexural capacity of rubberized concrete was smaller compared to the reduction in the compressive strength, due to the ability of the rubber to hold the integrity of the concrete microstructure. The incorporation of rubber shows improvement in the deformation capacity under bending (increased by 3%), due to its larger deformability and energy absorption property. The blended concrete with rubber shows the highest ductility due to the smaller particle size of pozzolana compared to cement. The crack pattern in the control and rubberized concrete appeared to be similar, indicating that the rubber did not alter the general concrete behaviour at the ultimate strength. Rubberized concrete could potentially be used for structural elements such as beams due to its acceptable strength and improved ductility.